(untitled) (Journal of Science and Technology, 2016)
A retrospective analysis of 105 cases of meningitis admitted at the Paediatric Department of Komfo Anokye Teaching Hospital, Kumasi between January 1987 and February 1988 is presented. The laboratory investigations show that 14 (13.3%) had clear CSF with negative culture. The biochemistry, cell count and type of cells were suggestive of viral meningitis. The remaining 91 (86.7%) cases had turbid CSF suggestive of bacterial infection. Hearing loss was found in 6.6% of children with bacterial meningitis.